39. RESULTS IN SOME PRIMARY HEALTH CARE ACTIVITIES AT MY LOC COMMUNE HEALTH STATION, HAU LOC DISTRICT, THANH HOA PROVINCE (2015 - 2023) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the results of the provision of an adequate supply of safe water and ensure environmental sanitation; appropriate treatment for common diseases and injuries; prevention and control of local endemic diseases at My Loc Commune Health Station, Hau Loc District, Thanh Hoa Province, during the period from years of 2015 to 2023.Methods: Analyze secondary data.Results: The proportion of households with wells, latrines, and bathrooms has gradually increased over the years, with average values of 94.3 ± 7.6%, 99.0 ± 2.9%, and 94.8 ± 8.7%, respectively, reaching 100% in many years. The average rate of medical examinations at the health station compared to the total number of examinations is 79.7 ± 5.1%, with outpatient treatments comprising 96.9%. The most common infectious diseases are influenza, diarrhea, and dysentery, with an average number of cases per year being 193, 6, and 3, respectively. Tuberculosis and leprosy have 1-2 cases per year. No instances of other infectious diseases were detected.Conclusion: Providing safe water and environmental sanitation activities have shown noticeable changes over time. The common healthcare services have demonstrated positive transformation, with the vast majority being outpatient treatments. The situation regarding endemic diseases is relatively stable, with no outbreaks occurring.
Keywords: Primary health care; Health station; My Loc commune.